Occupational Morbidity And Associated Risk Factors Among Agricultural Workers In India: Insights From Coimbatore And Beyond (International Journal of Environmental Sciences, 2025)
Agriculture is central to rural life in India, providing jobs for over 40% of the workforce and supporting nearly 70% of rural families. Even though agricultural workers play a key role in food production and the rural economy, they are among the most at-risk groups, facing high rates of illness and injury. This review synthesizes research and evidence from Coimbatore to highlight the health issues and risk factors that impact these workers. Common issues include joint and muscle pain, breathing problems, skin conditions, pesticide poisoning, heat stress, and diseases spread by water or insects. These health challenges are made worse by poverty, gender inequality, poor sanitation, and limited access to healthcare. Climate change and environmental damage add to these risks, making life even harder for this already vulnerable group. National policies have helped improve rural health through better sanitation, housing, and primary care, but the specific health needs of agricultural workers are still not well addressed in policy. Brazil and Vietnam demonstrate practical approaches to integrating agricultural health into rural healthcare. There is a clear need for coordinated, gender-aware, and climate-adapted actions to protect the health of India’s agricultural workers, who are vital to the country’s food supply and rural economy.